Electromyographic analysis of the superior belly of the omohyoid muscle and anterior belly of the digastric muscle in tongue and head movements - Castro, HAL; Resende, LAL; Berzin, F.; Konig, B. (Elsevier B.V., 1999)
The participation of the superior belly of the omohyoid muscle and anterior belly of the digastric muscle in tongue and head movements was studied eletromyographically in 20 normal young volunteers. A pair of monopolar electrodes was used in each muscle for simultaneous recording of their actions. The muscles act in the following tongue movements: protrusion, right and left lateral movements, placement of the tip of the tongue on soft and hard palates and on the floor of the mouth. The strongest levels of activity of the superior belly of the omohyoid muscle were observed in the placement of the tip of the tongue on the soft palate, coincidentally with a greater dislocation of hyoid bone. Both of the muscles studied did not participate in the head's kinesiology. (C) 1999 Elsevier B.V. Ltd. All rights reserved.
Keywords: electromyography; omohyoid muscle; digastric muscle